2023
DOI: 10.1021/acssuschemeng.2c04940
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Oxidation of Biomass Xylose to Formic Acid with CeOx-Promoted MnOx Catalyst in Water

Abstract: Formic acid is a versatile chemical, which is industrially produced from fossil resources. In this work, biomass-derived xylose was used as a potential feedstock to synthesize formic acid with Mn−Ce oxides as the catalyst in water. Among the Mn−Ce oxides with different molar ratios, Mn 4 Ce 0.05 O x showed the best catalytic activity, offering a formic acid yield up to 65.1% at 160 °C with 3 MPa of O 2 , which was much higher than that using pristine MnO x (40.5%) and CeO x (9.9%). In addition, Mn 4 Ce 0.05 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Formic acid (FA), being the most basic carboxylic acid, holds significant value as a chemical compound and has the potential to serve as an energy carrier. 113 It is highly desirable for FA to be derived from renewable sources such as biomass, as opposed to the current method reliant on fossil fuels. Guo et al 114 obtained a FA yield of 79% from glucose over Mo–MnO x at 160 °C in 90 min (Scheme 20).…”
Section: Sustainable Synthesis Of Value-added Chemicalsmentioning
confidence: 99%
“…Formic acid (FA), being the most basic carboxylic acid, holds significant value as a chemical compound and has the potential to serve as an energy carrier. 113 It is highly desirable for FA to be derived from renewable sources such as biomass, as opposed to the current method reliant on fossil fuels. Guo et al 114 obtained a FA yield of 79% from glucose over Mo–MnO x at 160 °C in 90 min (Scheme 20).…”
Section: Sustainable Synthesis Of Value-added Chemicalsmentioning
confidence: 99%
“…This work highlights the great potential of the Fenton reaction as a powerful and alternative tool for C−C bond cleavage. 163 Shen's group further investigated a series of Mn-based catalysts (MnO x -100, 164 Mn4Ce0.05O x , 166 and Mo-MnO x 167 ) to selective convert monosaccharide into formic acid. Among them, a manganese oxide (MnO x -100) catalyst prepared from hydrothermal treatment gave the highest formic acid yield of 81%, whereas Mo-modified Mo-MnO x showed high tolerance to the high concentration of glucose (110 g/L, 54% yield of formic acid).…”
Section: Keto-alcoholsmentioning
confidence: 99%
“…For Mn 4 Ce 0.05 O x , the adsorption energy of xylose on the Ce site was much lower than that on the Mn site, which favored the binding of xylose on the catalyst. 166 The reaction pathway was analyzed by monitoring the intermediates through ultraperformance liquid chromatography over a time course, where arabinose and glyoxylic acid were found to be the dominant intermediates during glucose conversion. 164 However, the stability of the developed Mnbased catalysts was not evaluated.…”
Section: Keto-alcoholsmentioning
confidence: 99%
“…Further studies are necessary to elucidate the Recently, oxidation systems of sugars to formic acid with non-vanadium catalysts have been reported. Feng Shen et al reported CeO 2 -and MoO x -modified MnO x catalysts for sugar oxidation to formic acid, and the obtained yields were 65.1 %-C from xylose [53] and 54 %-C from glucose, [54] respectively. Relatively severe conditions are necessary (433 K, 3 MPa O 2 ).…”
Section: Oxidation Of Carbohydrates To Formic Acid With Vanadium Cata...mentioning
confidence: 99%
“…Feng Shen et al. reported CeO 2 ‐ and MoO x ‐modified MnO x catalysts for sugar oxidation to formic acid, and the obtained yields were 65.1 %‐C from xylose [53] and 54 %‐C from glucose, [54] respectively. Relatively severe conditions are necessary (433 K, 3 MPa O 2 ).…”
Section: Oxidation Under Acidic Conditionsmentioning
confidence: 99%